2017
DOI: 10.1002/2016wr019873
|View full text |Cite
|
Sign up to set email alerts
|

Mixing layer and coherent structures in compound channel flows: Effects of transverse flow, velocity ratio, and vertical confinement

Abstract: Turbulent mixing layers associated with streamwise uniform and nonuniform flows in compound channels (main channel with adjacent floodplains) are experimentally investigated. The experiments start with uniform flow conditions. The streamwise nonuniformity is then generated by imposing an imbalance in the upstream discharge distribution between main channel (MC) and floodplains (FPs), keeping the total discharge constant, which results in a transverse depth‐averaged mean flow. This study first aims at assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 48 publications
16
59
0
Order By: Relevance
“…In rivers and streams, vegetated riparian zones in the streamwise direction are common. The vegetated areas induce flow resistance and influence the mean and turbulent properties of the flow, resulting in a velocity difference between the main channel and adjacent vegetation, which can result in a strong mixing layer [1,2]. The mixing layer plays an important role in redistributing momentum and mass between the main channel and vegetated areas [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rivers and streams, vegetated riparian zones in the streamwise direction are common. The vegetated areas induce flow resistance and influence the mean and turbulent properties of the flow, resulting in a velocity difference between the main channel and adjacent vegetation, which can result in a strong mixing layer [1,2]. The mixing layer plays an important role in redistributing momentum and mass between the main channel and vegetated areas [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The vegetated areas induce flow resistance and influence the mean and turbulent properties of the flow, resulting in a velocity difference between the main channel and adjacent vegetation, which can result in a strong mixing layer [1,2]. The mixing layer plays an important role in redistributing momentum and mass between the main channel and vegetated areas [1,3,4]. The mixing efficiency is expected to be affected by mean flow velocities and foliage, which regulates the suspended sediment load between the main channel and vegetated floodplain [3].…”
Section: Introductionmentioning
confidence: 99%
“…2). According to Proust et al [23] for compound channels, when the ratio based on the bulk velocities of the two sides = (U 1 − U 2 )∕(U 1 + U 2 ) > 0.3 , largescale turbulent structures with a vertical axis of rotation develop due to Kelvin-Helmholtz shear instability. Here, taking the effective bulk velocities U e,i , = {0.16, 0.44, 0.70} for h∕k = {3, 2, 1.5} , respectively, suggesting that h∕k = 2 and 1.5 could be subject to the Kelvin-Helmholtz shear instability.…”
Section: Kelvin-helmholtz Instabilitymentioning
confidence: 99%
“…These studies concluded that the growth of the shear layer is suppressed by the bottom friction and therefore, the exchange due to coherent turbulent structures is reduced for smaller depths, higher roughness and lower velocity difference between the parallel flows. On the other hand, Proust et al [23] showed that in a compound channel, where the velocity difference is sustained by the difference in the flow depth, the coherent structures persist even for very shallow conditions. Proust et al [23] proposed that these structures are controlled only by the difference in the bulk velocities over the flood plain, U 2 , and the main channel, U 1 , expressed as a velocity ratio (also referred to as dimensionless shear), = (U 1 − U 2 )∕(U 1 + U 2 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation